Sensory characterization of the perceived quality of East African highland cooking bananas (matooke) - Khakasa, E.; Muyanja, C.; Mugabi, R.; Bugaud, C.; Forestier-Chiron, N.; Uwimana, Brigitte; Arinaitwe, I.K.; Nowakunda, K. (Wiley, 2024)
BACKGROUND It has recently become increasingly evident that banana projects in Uganda need to consider consumer preferences as part of the breeding process to increase the acceptability of new cultivars. A trained panel used quantitative descriptive analysis (QDA) as a tool to assess the sensory characteristics of 32 cooking bananas (matooke). The aim was to investigate which sensory characteristics best describe matooke.